DASAR PERTIMBANGAN HAKIM TERHADAP PEMIDANAAN ANAK SEBAGAI PELAKU TINDAK PIDANA MENGEKSPLOITASI EKONOMI ATAU SEKSUAL ANAK - Diah Astiti Mataram, Cokorda Istri Agung; Ari Atu Dewi, A. A. Istri (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 05, November 2013)
The Economic or sexual exploitation child is a sexual act with respect to the child who can produce something such as money or satisfaction. Children as criminals or commit acts that are outlawed for children need to be dealt with carefully through the juvenile justice system. The problem that arises is what is the legal concept for judges in giving consideration to criminal punishment as a criminal child sexual exploitation and is there any special protection given to children as perpetrators of economic or sexual exploitation of children. Methods to address these problems is the juridical method for approaching the problem of empirical laws in force and the reality that exists in society and the nature of the descriptive analytical study. Of these problems was found that the judge impose punishment on children as perpetrators of criminal acts of economic or sexual exploitation of children using the legal concept of Code of Criminal Procedure, Law No.. 23 of 2002 on Child Protection, and Law No.. 3 1997 on the Juvenile Court, the child who has committed a criminal act of economic or sexual exploitation of children has been given special protection according stipulated in Law No.. 3 of 1997 on Juvenile Justice. The conclusion is that the judge in imposing punishment on children as perpetrators of economic or sexual exploitation apply legal concepts in the form of the Criminal Procedure Code, Law No.. 23 of 2003 on Child Protection, and Law No.. 3 1997 on the Juvenile Court and the children who commit crimes be given special protection are regulated according Law No.. 3 of 1997 on Juvenile Justice.
Keywords: Criminal Law, Sexual Exploitation, Punishment